Desafios e oportunidades para uma indústria espacial emergente: O caso do Brasil - Flávia de Holanda Schmidt (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– In recent decades, the design, development and use of space services has become an important economic pillar in several economies, where the increased magnitude of activities and space products and services gained importance in the process of economic and social development, not only in developed countries but also in emerging countries. In Brazil, despite the fact that the space sector have been regarded as one of three strategic sectors by the National Defense Strategy, important advances are still needed to take full advantages of the existing opportunities. This paper intends to add to the process of analysis of public policies regarding access to space and explotation of its benefits, as an initial step toward the production of technical documents that can assist in the improvement efforts of government action to the sector. In addition to outlining the context in which space activities are developed in the world, an overview of the Brazilian space industry is presented, through the analysis of companies in the domestic industry by descriptive statistics about the export and import and labor profile, which indicates that the sector differentiates in relation to other industries due to its technological intensity. A brief discussion of the key challenges identified for the national space industry is carried out, so that the sector can accommodate the strategic role intended by the Brazilian government through the National Defense Strategy.
Keywords: L10; L60; 330